2020
DOI: 10.1101/2020.06.12.147660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global FAW population genomic signature supports complex introduction events across the Old World

Abstract: Accurate genomic knowledge can elucidate the global spread patterns of invasive pests. The highprofile invasive agricultural pest Spodoptera frugiperda (fall armyworm; FAW) is a case in point. Native to the Americas, the FAW was first reported in West Africa in 2016 and has rapidly spread to over 64 countries across the Old World, resulting in significant economic losses. The chronological order of reported detections has led to the hypothesis that the FAW moved eastwards across Africa and then Asia, however g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 110 publications
(212 reference statements)
4
25
0
Order By: Relevance
“…One would be the uncharacteristic similarity between the ancestral population for all the invaded regions, which is indicative of a recent and a common source. Secondly, most of the earlier studies on FAW sequences in India have reported low levels of genetic variation, similar to the one found in Africa and East Asia [7,18,[21][22]. Thirdly, the distribution of the novel haplotypes in Indian populations is unimodal, typical of founder effect with recent population expansion.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…One would be the uncharacteristic similarity between the ancestral population for all the invaded regions, which is indicative of a recent and a common source. Secondly, most of the earlier studies on FAW sequences in India have reported low levels of genetic variation, similar to the one found in Africa and East Asia [7,18,[21][22]. Thirdly, the distribution of the novel haplotypes in Indian populations is unimodal, typical of founder effect with recent population expansion.…”
Section: Discussionsupporting
confidence: 51%
“…In fact, India, Africa and other regions of Asia shared common ancestral haplotypes and similar polymorphisms with each other, signifying a common source for all these populations. However, a recent study involving whole genome sequencing of FAW populations from New World and invaded regions has proposed multiple origins for FAW in the invaded countries [22]. On that basis, we think it would be prudent to analyse the diversity in Indian populations with multiple gene loci to conclusively trace the geographic origins or monitor the out ows from India.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations